Digital Scientist 2035—An Outlook on Innovation and Education - Barbazzeni, Beatrice; Friebe, Michael (Frontiers in Computer Science, 2021)
With the advent of the fourth industrial revolution accompanied by the Internet of Things, the implementation of smart technologies and digitalization already had a great impact in our society, especially when considering exponential innovation and human development. In this context, some types of employment have already been replaced or have been enhanced by the use of robots, human-machines interfaces and Artificial Intelligence systems. And there is likely more to come. If innovation can be viewed as a direct or indirect outcome of scientific research, which role will a scientist play in 2035? We developed a survey to investigate the opinions of scientists with respect to the possible future implementation of disruptive technologies, their feelings and approaches to digitalization, and particularly the impact of digital transformation on scientific education. In a futuristic scenario, we can imagine that scientists will be supported by technologies, carrying out numerous experiments, managing big datasets, producing accurate results, increasing communication, openness and collaboration among the worldwide scientific community, where ethics, regulations and social norms will always be observed. The new era of Digital Science is coming, in which humans will start to incorporate more disruptive and advanced technologies into their daily life; essential aspects for exponential innovation and development.